¿La Tendencia de la Masa Al Reposo? el Régimen Portaliano Enfrenta Al Mundo Plebeyo, 1830-1851 - Pinto-Vallejos, J (2011)
This article explores the visions of the "plebeian" sectors of Chilean society framed by the first two "Portalean" presidencies, as well as the policies and actions they devised with a view to popular "improvement". To that effect, it examines official pronouncements and initiatives related to the so-called "lower orders", reconstructing from there the counterpoint between the "real" people, normally both feared and repressed, and a fictional or desired people that would prove more pliable to Portalean notions of order and progress. The article closes with some thoughts on the underwhelming impact of those policies on their intended "targets", as well as the persistent disobedience or outright rejection of such official designs among significant segments of the working classes.